Campaign Inc. : How Leadership and Organization Propelled Barack Obama to the White House - De Sio, Henry F., 1962- (Book collections on Project MUSE., 2014)
It takes more than an excellent candidate to win elections; it takes an outstanding campaign organization, too. Campaign Inc. is the story of how leadership and organization propelled Barack Obama to the White House. As the chief operating officer of Obama's 2008 presidential campaign, Henry F. De Sio, Jr., was positioned to view this historic campaign as few others could. In this fascinating behind-the-scenes account, he whisks readers into Obama's national election headquarters in Chicago to glimpse the decision-making processes and myriad details critical to running a successful and innovative presidential campaign. From the campaign's early chaos to the jubilation and drama of winning the Iowa caucus, to the drawn-out Democratic nomination process, to Obama's eventual election as president of the United States, De Sio guides readers through the challenges faced by the Obama for America campaign in its brief twenty-one-month lifespan. De Sio shows readers that Obama himself was direct about his vision for the campaign when he instructed his staff to "run it like a business." Thus, this is less the story of Barack Obama, candidate, and more the story of Barack Obama, CEO. Because campaigns are launched from scratch during every election cycle, they are the ultimate entrepreneurial experience. In the course of the election, the Obama campaign scaled up from a scrappy start-up to a nearly 1 billion operation, becoming a hothouse environment on which the glare of the media spotlight was permanently trained. Campaign Inc. allows readers to peek behind the curtain at the underdog organization that brought down the Clinton campaign and later went on to defeat the Republican machine, while offering lessons in leadership and organization to innovators, executives, and entrepreneurs